Implementation and Challenges of Implementing the Independent Curriculum at SMK Negeri 5 Padang - Salsabila Nasution; Firman Firman; Mohd. Suhadi bin Mohammed Sidik; Naufal Zaky (Prophetic : Professional, Empathy, Islamic Counseling Journal, 2024)
The independent curriculum is a curriculum with a variety of intracurricular learning so that students can be more optimal and have concepts and strengthen their competencies. The aim of this research is to analyze information and challenges related to implementing the independent curriculum at SMK Negeri 5 Padang City. This research uses a descriptive qualitative research method whose data was obtained through observation and interviews with teachers at SMK Negeri 5 Padang. This research resulted that SMK 5 Padang had implemented an independent curriculum in accordance with the program that had been designed, the implementation process was carefully designed, this involved the principal, teachers and school staff. The implementation is not free from several challenges related to students only following the program mechanically, without fully understanding or internalizing the material, but these challenges are not an obstacle because SMK Negeri 5 itself has a solution by filling in evaluation and reinforcement sheets in the morning before the learning process takes place.